Utilização do farelo de côco em dietas para coelhos destinados ao abate - Haponik, Cecilia Aurea Vasconcelos de (2007)
This experiment was carried out with the objective of evaluating the effect of the inclusion of the coconut meal on the performance of rabbits on fattening diet. Initially, an essay of digestibility of coconut meal was made, using 18 animals distributed in a completely randomized design (CRD), in order to determine the digestibility coefficients of the nutrients and the energy of the food in rabbits. The performance lasted 11 days, being the latest 4 days for the excrement collections. The diets were composed of a reference ration and a test ration (30% of the reference ration). For the performance trial, 60 rabbits with 43 days of life had been used, distributed in a completely randomized design with 5 treatments, being 12 replicates for treatment. The experiment lasted 42 days. The treatments had consisted of the inclusion of coconut meal in the levels of 0; 6,25; 12,5; 18,75 and 25%. With the same structures and animals of this last performance, a digestibility trial of the diets whose delineation was the CRD was made, having 5 treatments with 3 replicates and an experimental unit of 4 rabbits. This experiment had duration of 5 days, in which the excrements had been collected. After the collections, the bromatological analysis and the determination of DE of excrements were made. It did not have significant effect (P>0,05) for the characteristics of weight gain, daily weight gain. There was a quadratic effect (P<0,05) for the total consumption, daily average consumption and feed conversion whose maximum values of inclusion of coconut meal are respectively: 14,07; 13,92 and 15%. Comparing the results gotten between the rations with coconut meal and the ration without coconut meal, it was observed that the total consumption and the average consumption of ration had differentiated from the control in the levels of 18,75 and 25%. Good digestibility of the crude energy and ether extract in the used diets was gotten. The average of the digestible energy between the diets was of 2510 DE (kcal/kg), however the digestibility of the crude protein presented low indices whose average was of 65, 07%. This way, it was concluded that the coconut meal in the condition of alternative food showed high values for CDGE, CDCP, CDEE, being able to be indicated in the diet until the 25% level, notably, in relation to food conversion and the diets with increasing levels of coconut meal it has the benefit of improved DE, however it presents reduction in the CDCP.